Thrombosis and Coagulopathy in COVID-19: Current Understanding and Implications for Antithrombotic Treatment in Patients Treated With Percutaneous Coronary Intervention - Liu, Hangkuan; Wang, Zhijia; Sun, Haonan; Teng, Tianming; Li, Yongle; Zhou, Xin; Yang, Qing (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease 2019 (COVID-19), a respiratory syndrome, is a global pandemic. Therefore, there is an urgent need to explore mechanisms implicated in the pathogenesis of the disease. Clinical and autopsy studies show a complex chain of events preceding COVID-19-related death. The disease is characterized by endothelial dysfunction, platelet activation, thrombosis, coagulopathy, and multiple organ failure. Globally, millions of patients with coronary heart disease undergo percutaneous coronary intervention (PCI) each year. These patients undergo high-intensity antithrombotic therapy during hospitalization and dual antiplatelet therapy (DAPT) for at least 6 months post PCI. COVID-19 is characterized by changes in platelet counts. Treatment of ischemic events that occur during stent implantation is associated with bleeding complications in patients following PCI complicated by COVID-19. This review summarizes recent progress in activation status and levels of COVID-19-related platelet changes. These findings will provide information on the effectiveness of antithrombotic therapy for the management of platelet changes in COVID-19 patients.